Robot milking and relationship with culling rate in dairy cows. (29th October 2018) - Bugueiro, A.; Fouz, R.; Camino, F.; Yus, E.; Diéguez, F. J.
Abstract : Cow routines and behavioral responses are altered substantially following the installation of robot milking. The present study was designed to analyze the effect that switching from milking parlor to automatic milking system (AMS) had on the culling rate (due to various causes) of dairy cattle. For this purpose, culling records and causes for culling were tracked in 23 dairy farms in the Galicia region (NW Spain). The animals in these farms were monitored for 5 years. For the present study, that length of time was divided into three different stages, as follows: 2 years before switching from a milking parlor to AMS (stage 1), the 1 st year following the implementation of AMS (stage 2) and the 2 nd and 3 rd years succeeding the implementation of AMS (stage 3). Cox models for survival analysis were used to estimate the time to culling due to different reasons during stage 1 in relation to stages 2 and 3. The data indicated that the risk of loss due to death or emergency slaughter decreased significantly following the installation of AMS. In contrast, the risk of culling due to low production, udder problems, infertility or lameness increased significantly. Low-production cows (such as cows in advanced lactation due to infertility) or sick cows (such as mastitic or lame cows) allegedly have a noticeable effect both on the performance and the amortization of the cost of AMS, which in turn would lead to a higher probability of elimination than in conventional systems.